Caiman Breeding in Captivity at Kukrail - , Ashok; Misra, S. B. (Indian Forester, 1990)
Studies were conducted on Caiman breeding in captivity at Kukrail which were brought out from Madras Crocodile Bank. It was found that the batching success of Crocodilian eggs under captive condition was quite favourable and survival rate depends upon tbe congenital characters of individual.